Advancements in temporomandibular joint total joint replacements (TMJR) - Mamidi, Siva Kumar (Biomed Eng Lett, 2019)
The goal of this paper is to review the advantages and disadvantages of the various treatment options of temporomandibular joint (TMJ) total joint replacement (TJR). TMJ articles published within the last 20 years were reviewed to collect the information on non-invasive and invasive TMD treatment methods. Recent technological advancements helped the evolution of treatment methods and offered significant value to TMD patients and surgeons. Considering the TMD levels, the therapeutic procedures can involve general health examiniations, physical therapy, medication, oral rehabilation or as an end stage clinical invention, temporomandibular joint replacement. In fact when intra-articular TMD is present, the effective treatment method appears to be TJR. However, concern for infection, material hypersensitivity, device longevity and screws loosening issues still exists. Further combined research utilizing the knowledge and expertise of, surgeons, material scientists, and bioengineers is needed for the development of improved TMD therapeutic treatment.